A simple PMMA phantom for daily QA energy checks in proton therapy. (September 2016) - Bizzocchi, N.; Fracchiolla, F.; Schwarz, M.
Abstract : Introduction: Beam energy measurements are one of the most important data that every radiotherapy facility has to collect periodically as constancy check. In proton therapy, due to the energy selection system and to the shape of the Bragg peak, this check has to be performed daily. Purpose: To demonstrate that reliable daily proton energy verification is achievable using a 2D array of ionization chambers (IC) combined with our PMMA phantom. Material and methods: The PMMA phantom is provided with three couples of wedges: thanks to these, Bragg peak is sampled at different depths and the image becomes a transposition on the transverse plane of the depth dose. Coupled wedges are necessary to compensate for set-up errors. Three wedges of different slopes (the first and lowest one is for energy from 70 to 100 MeV, the middle one from 100 to 140 MeV and the third and highest one from 140 to 226 MeV) are used to spread the depth dose of every single checked energy in a way that the distal penumbra can be properly detected by an adequate number of IC in the 2D Array device. Results: A sensitivity test showed that the phantom is able to detect range variations greater than the threshold (2 mm). Conclusions: We designed and built a reliable phantom for the range verification. Moreover, the costs of this phantom are very low compared to other commercial solutions used for range verification in proton therapy.